2011
DOI: 10.1159/000324832
|View full text |Cite
|
Sign up to set email alerts
|

Selective, α2β1 Integrin-Dependent Secretion of IL-6 by Connective Tissue Mast Cells

Abstract: Mast cells, critical mediators of inflammation and anaphylaxis, are poised as one of the first lines of defense against external assault. Mast cells release several classes of preformed and de novo synthesized mediators. Cross-linking of the high-affinity FcΕRI results in degranulation and the release of preformed, proinflammatory mediators including histamine and serotonin. We previously demonstrated that mast cell activation by Listeria monocytogenes requires the α2β1 integrin for rapid IL-6 secretion both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…Nishida et al [67•] demonstrated that the presence of Gab2 affects mast cell degranulation, but not cytokine production, and demonstrated different requirements for the development of IgE-mediated anaphylaxis versus contact hypersensitivity. Differential regulation of mast cell degranulation and cytokine production, specifically IL-6, with distinct stimuli, resulting in the release of specific mediator pools, has also been demonstrated by McCallCulbreath et al [68].…”
Section: Regulation Of Fcεri Signalling Mast Cell Function and Medimentioning
confidence: 64%
“…Nishida et al [67•] demonstrated that the presence of Gab2 affects mast cell degranulation, but not cytokine production, and demonstrated different requirements for the development of IgE-mediated anaphylaxis versus contact hypersensitivity. Differential regulation of mast cell degranulation and cytokine production, specifically IL-6, with distinct stimuli, resulting in the release of specific mediator pools, has also been demonstrated by McCallCulbreath et al [68].…”
Section: Regulation Of Fcεri Signalling Mast Cell Function and Medimentioning
confidence: 64%
“…L. monocytogenes and specifically the pore-forming toxin LLO [23], cause mast cell degranulation in vivo [24] and in vitro [3]. Mast cells have also been shown to release cytokines directly in response to L. monocytogenes under various conditions [6], [7], [9], [10], [24]. We therefore focused on further investigating the effect of L. monocytogenes on mast cell activation, specifically mast cell degranulation and mediator release.…”
Section: Resultsmentioning
confidence: 99%
“…During degranulation, pre-formed tumour necrosis factor-α (TNF-α) is released resulting in the recruitment and activation of neutrophils [3], [6]. TNF-α, however, is just one of the cytokines released in response to L. monocytogenes with other pro-inflammatory cytokines, including IL-6 and IL-1β, released during infection in vivo [7], [8], and mast cells have been shown to secrete these in response to L. monocytogenes in vitro [7], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies and recent evidence from the a2b1 integrin-deficient mice indicated that although osteoclasts may express a2b1 integrin, it seems that their function depends more on avb3 integrin rather than on a2b1 and other integrins (43,44). In contrast, a2b1 integrin has been shown to regulate mast cell activation (45,46), and mast cells have been associated with the pathogenesis of arthritis (47). Although mast cells are not required in the model of CIA used in this study (48), the earlier findings suggest that a2 integrin blockade can also affect mast cell activity during the course of arthritis and, therefore, contribute to the reduction of arthritis severity.…”
Section: Discussionmentioning
confidence: 99%